The influence of Green Creativity and Green transformational leadership on Environmental Performance - Dewanti, Mentari Clara; Rosyanti, Daisy Marthina; Khoirotunnisa, Fani (Nusantara Science and Technology Proceedings, 2023)
The development of more ecologically friendly goods, methods, and technologies is encouraged by green creativity. Inadequate use of natural resources, greenhouse gas emissions, and air and water pollution can all be reduced as a result. The goal of the leadership strategy known as "Green transformational leadership" aims to establish a work environment that prioritizes environmental friendliness and sustainability. The research methodology involves quantitative analysis paired with linear regression. The demographic and sample for the study comprise employees from 4-star hotels in East Java, totaling 85 individuals. Through initiatives such as reducing adverse effects, fostering sustainable innovation, enhancing awareness, and ensuring compliance with environmental regulations, green creativity significantly enhances environmental performance